2022
DOI: 10.3390/a15080275
|View full text |Cite
|
Sign up to set email alerts
|

New Step Size Control Algorithm for Semi-Implicit Composition ODE Solvers

Abstract: Composition is a powerful and simple approach for obtaining numerical integration methods of high accuracy order while preserving the geometric properties of a basic integrator. Adaptive step size control allows one to significantly increase the performance of numerical integration methods. However, there is a lack of efficient step size control algorithms for composition solvers due to some known difficulties in constructing a low-cost embedded local error estimator. In this paper, we propose a novel local er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It has been shown that explicit approaches can be more effective even when tiny time step sizes are required [20]. Moreover, various ingenious combinations of explicit and implicit methods, such as semi-explicit or semi-implicit methods, have also been presented [21][22][23][24]. However, they do not really solve the problems and the drawbacks of the explicit and implicit approaches discussed above.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that explicit approaches can be more effective even when tiny time step sizes are required [20]. Moreover, various ingenious combinations of explicit and implicit methods, such as semi-explicit or semi-implicit methods, have also been presented [21][22][23][24]. However, they do not really solve the problems and the drawbacks of the explicit and implicit approaches discussed above.…”
Section: Introductionmentioning
confidence: 99%
“…Beuken et al [24] constructed versions of these methods based on the backward differentiation formula and Adams-Bashforth schemes for ODE systems, which can be an order of magnitude faster than some traditional methods. Fedoseev et al [25] improved the performance of semi-implicit composition integration methods by variable step size control algorithms. The paper of Ji and Xing [26] proposes a set of time-marching methods which uses the generalized Padé approximation, the Gauss-Legendre quadrature, and explicit Runge-Kutta schemes to solve systems of ODEs.…”
Section: Introductionmentioning
confidence: 99%